2009
DOI: 10.5604/20831862.890152
|View full text |Cite
|
Sign up to set email alerts
|

Absolute lactate threshold predicts endurance performance in master athletes

Abstract: Abstract. In master athletes the relationship between lactate threshold (LT) and endurance performance is unclear, possibly due to age-related decrease in VO 2 peak. To determine whether an absolute measure of LT was a significant predictor of 10km running performance in master athletes, 51 men master athletes (40-77 yrs) performed a treadmill graded exercise test with minute-by-minute venous blood samples for lactate analysis. Training status and recent 10 km performances were determined by questionnaire. VO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The discrepancies between studies may be connected with different methods for threshold determination as well as age ranges, training status, and study design. It was also found that that absolute but not relative LT was a significant predictor of performance in master athletes (32). Therefore, the diagnostic and clinical value of percentage threshold values is questionable.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The discrepancies between studies may be connected with different methods for threshold determination as well as age ranges, training status, and study design. It was also found that that absolute but not relative LT was a significant predictor of performance in master athletes (32). Therefore, the diagnostic and clinical value of percentage threshold values is questionable.…”
Section: Discussionmentioning
confidence: 97%
“…Untrained individuals (UT) very seldom undergo invasive tests to identify the LT, i.e., the exercise V O 2 above which a net increase in lactate production is observed, resulting in a sustained increase in blood lactate concentration (16). In aging competitive athletes and physically active elderly people, VT is also determined (6,21,34,39), but the majority of examinations rely on LT identification (1,22,23,32,38) and on the determination of maximal lactate steady state, i.e., the highest concentration of blood lactate that can be maintained during the last 20 min of a 30-min constant-workload test, representing an equilibrium between lactate production and clearance (24). According to all given results, regardless of the variety of methods and controversies about relation between VT and LT and their metabolic basis (2,15,27), a significant decline in absolute threshold parameters with age is observed in any case.…”
mentioning
confidence: 99%
See 1 more Smart Citation